Manutenção do comportamento obsessivo-compulsivo por interações familiares: levantamento de algumas variáveis por meio de observação - Almeida, Tatiana Araujo Carvalho de (2005)
From a behavior analytic perspective, the obsessive-compulsive behaviors (OCB) are understood as being controlled by environmental variables interacting with the behaving organism. This study aimed to describe the family interactions that could be controlling the emission of these behaviors through interviews with the persons involved and through direct observation. The participants were a fifteen year-old teenager who presented OCB and his mother (the only family member living with him). This research was developed in two stages. First, interviews with both participants were carried out. The goal of the interviews was to survey the controlling variables of OCB and get more information about the habits of the family and the house. On the second stage of the research, the behaviors of the participants (obsessive-compulsive behaviors and other related behaviors) were observed, which lasted for twenty-two days. Four video cameras were installed in the participants house. The purposes of the video recording were: 1) to check if the verbal descriptions obtained through the interviews would be observed in the family s daily routine; 2) to identify other controlling variables of OCB not clear in the interviews. The main results found were: 1) the number of responses emitted by the teenager classified as obsessive and/or compulsive was high when compared to the number of his responses classified as socially appropriate and inappropriate; 2) the percentage of responses classified as obsessive and/or compulsive emitted when the mother was present was higher (59% of the recorded responses) than the percentage of the responses emitted in the absence of the mother (40,5% of the recorded behaviors). The mother was present when 84% of the responses classified as socially inappropriate were emitted, and when 72,1% of the responses classified as socially appropriate were emitted. The mother was absent in 15,4% of the responses classified as socially inappropriate and in 27,9% of the responses classified as socially appropriate; 3) 57% of the responses classified as obsessive and/or compulsive were followed by the mother s attention and after 43% of the responses, the mother behaved as to withdrawn attention as a consequence of his child s behavior. The difference between the number of responses followed by attention (higher number) and the number of responses followed by lack of attention (lower number) was repeated for the groups of responses classified as socially appropriate and socially inappropriate. The results confirm what has been shown by studies in the field, that is, the family is an important controlling variable in the maintenance of OCB